2021
DOI: 10.2139/ssrn.3926273
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and factors for agricultural use of sludge in circular Bulgarian economy

Abstract: The issue of utilization of sludge from wastewater treatment in agriculture is an important socio-economic and environmental problem in the European Union and Bulgaria. Its significance is determined by the fact that the amount of sludge formed is constantly growing, as the annual amount of sludge produced in Europe is 8.7 million dry matter, and in Bulgaria reaches 53 thousand tons of dry matter. One of the main ways to utilize sludge from wastewater treatment in its use as fertilizer in agriculture. It is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, the authors found that during this period, the number of journals where the results of research on this topic were published increased from 39 to 1028 [40]. It should be recognized that due to the fact that the very concept of "a circular economy" is interdisciplinary, as well as the fact that the essence and goals of a circular economy development are considered at the global level, at macro-and mesolevels [41][42][43][44][45][46][47][48][49], the scientific research on the problems of forming the systems of monitoring in the context of a circular economy development at the micro level is practically absent. Despite this, there are studies of the circular economy of the systems of monitoring at the macro -and meso-levels.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the authors found that during this period, the number of journals where the results of research on this topic were published increased from 39 to 1028 [40]. It should be recognized that due to the fact that the very concept of "a circular economy" is interdisciplinary, as well as the fact that the essence and goals of a circular economy development are considered at the global level, at macro-and mesolevels [41][42][43][44][45][46][47][48][49], the scientific research on the problems of forming the systems of monitoring in the context of a circular economy development at the micro level is practically absent. Despite this, there are studies of the circular economy of the systems of monitoring at the macro -and meso-levels.…”
Section: Introductionmentioning
confidence: 97%
“…However, they are also a rich source of nitrogen, phosphorus, and organic matter, as well as essential trace elements [3,4]. Although various sludge treatment methods exist and are implemented, e.g., incineration, landfill [2,5], and recycling into building materials [1], an increasingly necessary application is its utilization in agriculture because of its high fertilization value [2,[5][6][7][8]. The chemical characterization of the sludge before its reuse is a key requirement in the principles of circular economy for development of appropriate technologies for processing and recycling of the waste material.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there are many issues related to the technological introduction of sludge in arable agricultural land and a lack of public acceptance of sludge utilization in agriculture. There are also other research papers focused on environmental [28,29], economic [29,30] and various other [31,32] indicators.…”
Section: Introductionmentioning
confidence: 99%